The Great Convergence VS. The Great Divergence - Zheng, Yongnian. author. aut Link
XVII, 285 p. 2 illus., 1 illus. in color.
Keywords: This book explores what's happening in international affairs and whether the changes will bring opportunity or crisis to China's modernization. How can China reverse the trend of anti-globalization and lead a new wave of globalization? How can Chinese thinkers bring about another great convergence of globalization and modernization? In-depth thinking about these questions and answering them form the theme of this book. This book puts the main focus on clarifying the relationship between China’s modernization process and economic globalization, exploring the deep-seated reasons for the momentous world changes and the great challenges they have posed to the China’s continued modernization. In particular, it answers the question “What is China’s next step?”, providing the readers with profound insights and forward-looking thinking to understand the changing situation of the world and grasp the future of China. Professor Zheng Yongnian is a renowned Chinese political scientist and political commentator who has written widely on contemporary China and especially Chinese politics. He received his B.A. and M.A. from Beijing University and his Ph.D. at Princeton University. He was a recipient of Social Science Research Council-MacArthur Foundation Fellowship and John D. and Catherine T. MacArthur Foundation Fellowship. He currently serves as Presidential Chair Professor and the Founding Dean of School of Public Policy, and Funding Director of the Institute for International Affairs, the Chinese University of Hong Kong, Shenzhen.